Molecular detection and distribution analysis of papaya ringspot virus-p in North Sumatra, Indonesia - Harahap, Lenny Hartati; Bakti, Darma; Lisnawita, Lisnawita; Tantawi, Ahmad Rafiqi (Asian Journal of Agriculture and Rural Development, 2025)
The Papaya Ringspot Virus-P (PRSV-P) presents a significant threat to papaya cultivation, especially due to inter-island fruit trading, which facilitates its rapid spread. In North Sumatra, PRSV-P has caused substantial damage to papaya plantations, resulting in decreased fruit yields. This research aimed to elucidate the bio-ecological and molecular characteristics of PRSV-P in papaya, emphasizing its potential seedborne transmission route. Field assessments were performed in Deli Serdang, Dairi, and Pakpak Bharat, where symptomatic plants exhibited dark green ring spots on fruits and mosaic patterns on foliage. Samples were analyzed with DAS-ELISA, RT-PCR, and nucleotide sequencing, while a synthesized infectious PRSV-P clone was manually introduced into juvenile pepper plants to confirm pathogenicity. DAS-ELISA validated infections in leaf and seed specimens, while RT-PCR analysis identified elevated proportions of whole viral genomes. Sequence analysis revealed over 99% nucleotide and amino acid identity with PRSV-P strains from Bali and Thailand, signifying a close genetic affinity. The detection of PRSV-P in papaya seeds constitutes the initial molecular evidence of seed transmission in North Sumatra and indicates a possible method for long-distance dispersal independent of insect vectors or vegetative propagation. These findings highlight the imperative to incorporate molecular diagnostics into monitoring initiatives and to implement effective management techniques, including seed health assessments, creation of resistant cultivars, and stringent phytosanitary protocols. This study underscores the pivotal significance of seed transmission in the epidemiology of PRSV-P and its ramifications for sustainable papaya cultivation in Indonesia.